Nanoscale Zinc Oxide Particles for Improving the Physiological and Sanitary Quality of a Mexican Landrace of Red Maize - Juan Estrada-Urbina; Alejandro Cruz-Alonso; Martha Santander-González; Abraham Méndez-Albores; Alma Vázquez-Durán (Nanomaterials, 2018)
In this research, quasi-spherical-shaped zinc oxide nanoparticles (ZnO NPs) were synthesized by a simple cost-competitive aqueous precipitation method. The engineered NPs were characterized using several validation methodologies: UV–Vis spectroscopy, diffuse reflection UV–Vis, spectrofluorometry, transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and Fourier transform infrared (FTIR) spectroscopy with attenuated total reflection (ATR). A procedure was established to coat a landrace of red maize using gelatinized maize starch. Each maize seed was treated with 0.16 mg ZnO NPs (~7.7 × 109 particles). The standard germination (SG) and accelerated aging (AA) tests indicated that ZnO NP-treated maize seeds presented better physiological quality (higher percentage of normal seedlings) and sanitary quality (lower percentage of seeds contaminated by microorganisms) as compared to controls. The application of ZnO NPs also improved seedling vigor, correlated to shoot length, shoot diameter, root length, and number of secondary roots. Furthermore, shoots and roots of the ZnO NP-treated maize seeds showed a marked increment in the main active FTIR band areas, most notably for the vibrations associated with peptide-protein, lipid, lignin, polysaccharide, hemicellulose, cellulose, and carbohydrate. From these results, it is concluded that ZnO NPs have potential for applications in peasant agriculture to improve the quality of small-scale farmers’ seeds and, as a result, preserve germplasm resources.